Exploring the effect of surface chemistry and particle size of boron-doped diamond powder as catalyst and catalyst support for the oxygen reduction reaction. (1st April 2023) - Alemany-Molina, Gabriel; Martínez-Sánchez, Beatriz; Gabe, Atsushi; Kondo, Takeshi; Cazorla-Amorós, Diego; Morallón, Emilia
Abstract: The interest for the electrodes based on conductive boron-doped diamond powder (BDDP) is increasing in recent years due to their excellent physical and chemical stability, the wide potential window in both aqueous and organic electrolytes, the relatively large specific surface area, and their versatility in comparison to boron-doped diamond thin film electrodes. These materials have been proposed as alternative cathode catalyst support due to their high corrosion resistance when subjected to the highly positive potentials originated during the start-stop operations in fuel cells, especially in automobiles. In this work, we present three BDDP supports with different particle sizes and different surface oxygen contents as supports of different iron species for oxygen reduction reaction in alkaline solution. BDDP supports were modified with carbon nitride (C3 N4 ) or phthalocyanines (Pc) as anchoring points for iron. The different electrocatalytic performance observed confirmed the strong influence of the surface chemistry of the BDDP supports on the activity of the metallic sites for FePc samples while, for Fe-C3 N4 samples, the determining effect was the particle size of the BDDP support. Additionally, DFT calculations were used to obtain some insights about the interaction of the FePc with the diamond surface.